Analysis of Heavy Equipment Productivity in the Construction of the Surabaya State Polytechnic Integrated Lecture Building Project - Zulfar, Mochamad Ilham; Fernanda Arya Pramudya; Aulia Dewi Fatikasari (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2025)
Building construction is intensively carried out in Indonesia. That is because Indonesia is a developing country that needs quite a lot of infrastructure, be it buildings, offices, roads, bridges, or ports, especially at the Surabaya State Shipbuilding Polytechnic which is building an Integrated Lecture Building. The development process certainly does not escape the need for heavy equipment, such as excavators. Heavy equipment is a crucial requirement in building construction projects, this is because heavy equipment is a means of supporting work in the project, for example excavation work. Because excavators are important tools in building construction projects, it is necessary to analyze the productivity of heavy equipment. This study aims to analyze the productivity of excavators so that they can improve operational efficiency, save costs, and determine the duration of work.